ESTIMASI KERUGIAN EKONOMI AKIBAT OBESITAS PADA ORANG DEWASA DI INDONESIA - Wulansari, Arnati; Martianto, Drajat; Baliwati, Yayuk Farida (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2016)
This study was aimed to estimate economic loss due to obesity among adults in Indonesia. Estimating of economic loss due to obesity was measured by calculating cost of health care, cost of productivity loss due to premature death, and cost of productivity loss due to absenteeism. Health care cost was estimated by multiplying the proportion of incidence of comorbidity in obese population, population of obese, and maintenance costs. Cost of productivity loss due to premature death was calculated by using the number of deaths, labour force participation rate, and annual wages, then divided by discount rate rank expected years of life lost. Cost of productivity loss due to absenteeism was calculated by using population of obese, the number of days absent from work, labour force participation rate, and daily wages. Health care cost in Indonesia was estimated at Rp 56,487 billion/year. Cost of productivity losses due to premature death was estimated at Rp 1,597 billion/year. Cost of productivity losses due to absenteeism estimated at Rp 20,394 billion/year. The total cost of obesity was then estimated at Rp 78,478 billion/year (0,9% of Indonesia’s GDP in 2013).